Support of the Internet of things for energy transformation - Yusheng XUE; Hongbo ZHU; Qin WANG; Haitao ZHAO (物联网学报)
The trend of energy transformation is to integrate smart grid into comprehensive energy.The research method is to establish the framework of energy information,physics and social system research.The active support of power transformation is the guarantee of the success of energy transformation.The proposed scheme emphasized the importance of social factors in practical engineering and research.As a new research methodology,it was compatible with mixed simulation of data,model and behavior.The widely used method in engineering was extended to economics and sociology,and the decision-making method based on subjective experience was made more scientific.In addition,in the definition of the Internet of things,the idea of removing the limitations of the Internet was proposed,and a unified framework was used to reflect the impact of the combination of the Internet/private network and other technologies.